2019
DOI: 10.1002/ccr3.2144
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyllum pinnatum in the treatment of restless legs syndrome: A case series documented with polysomnography

Abstract: Key Clinical Message Restless legs syndrome may seriously affect patients' sleep and quality of life, but established pharmacological therapy can often have severe side effects. Therefore, new therapeutic approaches such as well‐tolerated preparations from the medicinal plant Bryophyllum pinnatum should be considered as alternatives. Their sedative and spasmolytic properties might contribute to improve patients' condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Seeds of Vigna radiata were used for this investigation. Four different concentrations (25,50,75, and 100 μg/mL) of SiNPs were prepared using distilled water. The seeds were surface sterilized using distilled water.…”
Section: Agricultural Applications Seed Germination Analysismentioning
confidence: 99%
“…Seeds of Vigna radiata were used for this investigation. Four different concentrations (25,50,75, and 100 μg/mL) of SiNPs were prepared using distilled water. The seeds were surface sterilized using distilled water.…”
Section: Agricultural Applications Seed Germination Analysismentioning
confidence: 99%
“…In 2010, Bryophyllum preparations were already frequently used by anthroposophic physicians in Germany for the treatment of mental and behavioural disorders such as sleep disorders, anxiety, and depressive symptoms [2]. Since then, three prospective trials and one case series reported improved sleep quality during treatment with B. pinnatum (50% chewable tablets): during pregnancy [12], in cancer [13], associated with restless legs syndrome [14] and with nocturia [8]. Although little is known about possible mechanisms of action that would support its use in the treatment of mental and behavioural disorders, some results from animal models support a CNS depressant action, as well as sedative and anxiolytic effects [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, its use during pregnancy to prevent preterm uterus contractions is well established [ 20 , 21 ], and uterus-relaxant properties have been proven at both the tissue [ 22 , 23 ] and cell level [ 24 , 25 ]. Some clinical studies have revealed its potential in the treatment of sleep disorders, be they during pregnancy [ 26 ] or associated with other diagnoses [ 27 , 28 ]. Its use in these indications corresponds well to the sedative, central nervous system depressant, and anxiolytic properties that have been shown in animal models, namely rats, mice [ 29 ], and zebra fish [ 30 ].…”
Section: Introductionmentioning
confidence: 99%